1989
DOI: 10.1063/1.100953
|View full text |Cite
|
Sign up to set email alerts
|

New gettering using misfit dislocations in homoepitaxial wafers with heavily boron-doped silicon substrates

Abstract: The gettering mechanism due to misfit dislocations in P/P+ epitaxial wafers is clarified for copper-diffused epitaxial wafers. The epilayer thickness of the sample is 2.2 μm and the substrate resistivity of the sample is 0.0015–0.002 Ω cm. It is dipped in a Cu(NO3 )2 -HF solution and annealed at 900 °C for 30 min. The in-depth Cu profile obtained by secondary-ion mass spectroscopy shows a distinctive peak at the P+ -substrate side in the vicinity of the epi/sub interface. This peak coincides with that of dislo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…10 The DSB interface was reported to have screw dislocations along the ͗110͘ direction coming from the inevitable misorientation between Si ͑110͒ and ͑100͒ substrates. 30 However, our calculations revealed that the coherent region of the DSB interface is also an efficient gettering site. That is, the smaller results in the larger interval.…”
Section: Gettering Efficiencymentioning
confidence: 71%
“…10 The DSB interface was reported to have screw dislocations along the ͗110͘ direction coming from the inevitable misorientation between Si ͑110͒ and ͑100͒ substrates. 30 However, our calculations revealed that the coherent region of the DSB interface is also an efficient gettering site. That is, the smaller results in the larger interval.…”
Section: Gettering Efficiencymentioning
confidence: 71%
“…Such gettering effects have been invoked in a number of papers [6,14-201. In particular, striking observations of impurity segregation at dislocations were reported by Marek et al [16] on GaAs wafers, by using a PL imaging technique of very high spatial resolution, and by Sekiguchi and Sumino [I71 in CL imaging. Also, direct observations by transmission electron microscopy (TEM) of segregation around misfit dislocations in silicon epitaxial structures, were reported by Lee et al [I91 and Kikuchi et al [20].…”
Section: Introductionmentioning
confidence: 91%
“…Misfit dislocations are generated at the interface between the epitaxial layer and the low concentration substrate by mismatch of the lattice constant. However, it has been reported that misfit dislocations do not reduce the device performance [2]. Figure 5(b) shows an X-ray topography image of a wafer that has undergone a slip dislocation acceleration process, in which the rate of temperature change is increased.…”
Section: Influence Of Bulk Micro Defectsmentioning
confidence: 97%